2014
DOI: 10.7314/apjcp.2014.15.2.917
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-100 Resensitizes Resistant Chondrosarcoma Cells to Cisplatin through Direct Targeting of mTOR

Abstract: Chondrosarcomas are malignant cartilage-forming tumors of bone which exhibit resistance to both chemotherapy and radiation treatment. miRNAs have been well demonstrated to regulate gene expression and play essential roles in a variety of biological processes, including proliferation, differentiation, migration, cell cycling and apoptosis. In this study, we obtained evidence that miR-100 acts as a tumor suppressor in human chondrosarcomas. Interestingly, cisplatin resistant chondrosarcoma cells exhibit decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 32 publications
(41 reference statements)
2
26
0
1
Order By: Relevance
“…27,28 Several researches proved that overexpression of miR-100 can sensitize cancer cells to DDP in various tumors. 23,29 Concurring with these studies, our research confirmed that the downregulated expression of miR-100-5p contributed to DDP resistance in lung cancer cells. The luciferase reporter in previous literatures 22,23 proved that mTOR is a direct target gene of miR-100-5p and can be regulated by directly binding to the 3′-UTR of mTOR.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…27,28 Several researches proved that overexpression of miR-100 can sensitize cancer cells to DDP in various tumors. 23,29 Concurring with these studies, our research confirmed that the downregulated expression of miR-100-5p contributed to DDP resistance in lung cancer cells. The luciferase reporter in previous literatures 22,23 proved that mTOR is a direct target gene of miR-100-5p and can be regulated by directly binding to the 3′-UTR of mTOR.…”
Section: Discussionsupporting
confidence: 64%
“…23,29 Concurring with these studies, our research confirmed that the downregulated expression of miR-100-5p contributed to DDP resistance in lung cancer cells. The luciferase reporter in previous literatures 22,23 proved that mTOR is a direct target gene of miR-100-5p and can be regulated by directly binding to the 3′-UTR of mTOR. In our study, we did find that mTOR expression was negatively regulated by miR-100-5p, thereby modulating the sensitivity of lung cancer cells to DDP.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Deregulation of miR-100 has been reported in drug resistance; however, miR-100 expression can be either over-expressed or under-expressed in diverse cancers (134). In ovarian cancer, miR-100 targets mTOR therefore reverting the cell's chemoresistance toward cisplatin (135) and chondrosarcoma (136). In pancreatic cancer, miR-100 mimics inhibit proliferation and increase sensitivity to cisplatin by targeting FGFR3 (137).…”
Section: A Network Analysis: the Most Central Ncrnas In Chemoresistancementioning
confidence: 99%
“…For example, Li et al reported that transfection of lentivirual vector containing miR-100 mimics in pancreatic cancer cells could inhibit cancer cell proliferation and increase sensitivities to cisplatin through targeting FGFR3 [42]. Zhu et al also highlighted miR-100 as a tumor suppressor in chondrosarcoma and obtained evidence that overexpression of miR-100 could reverse the chemoresistance of cisplatin-resistant chondrosarcoma cells to cisplatin by directly targeting mTOR [74]. In addition, upregulated miR-100 with oncogenic potential in specific cancer types can be potential therapeutic targets for inhibition by using antisense oligonucleotides, sponges or locked nucleic acid (LNA) constructs [144][145][146].…”
Section: Mir-100 In Cancer Therapymentioning
confidence: 99%